2022
DOI: 10.1111/hsc.13945
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and lung cancer screening: Prioritising a humanistic approach to care

Abstract: Low‐dose computed tomography lung cancer screening has mortality benefits. Yet, uptake has been low. To inform strategies to better deliver and promote screening, in 2018, we interviewed 27 long‐term smokers immediately following lung cancer screening in Australia, prior to receiving scan results. Existing lung screening studies employ the Health Belief Model. Reflecting growing acknowledgement of the centrality of emotions to screening uptake, we draw on psychological and sociological theories on emotions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…Instead of invoking or reinforcing narratives of responsibilisation and choice, campaigns would be better served by narratives which resist stigma: by positioning smokers as victims of circumstance and addiction. It is noteworthy that nearly all interviewees in our study started smoking in their teens, many in their early teens (Olson et al, forthcoming; Charles). Emphasising that many long-term smokers are trapped in addictive habits that began early in life, would serve to medicalise smoking (Furedi, 2008), positioning smokers as victims of circumstance, in need and deserving of care (Mol, 2008).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Instead of invoking or reinforcing narratives of responsibilisation and choice, campaigns would be better served by narratives which resist stigma: by positioning smokers as victims of circumstance and addiction. It is noteworthy that nearly all interviewees in our study started smoking in their teens, many in their early teens (Olson et al, forthcoming; Charles). Emphasising that many long-term smokers are trapped in addictive habits that began early in life, would serve to medicalise smoking (Furedi, 2008), positioning smokers as victims of circumstance, in need and deserving of care (Mol, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Here, we analyse the storied experiences of smoking and smoking cessation that attend to the moral challenge posed by stigma (Broom and Whittaker, 2004; Rance et al, 2017). Findings on participants’ experiences of lung screening are reported elsewhere (Olson et al, forthcoming). Our approach offers insight into ‘contradictory layers of meaning’ and the interplay between the personal and rhetorical (Andrews et al, 2008: 1; Clandinin and Rosiek, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Significant barriers to LCS uptake have been identified, including practical barriers (travel time and associated costs, work and/or career responsibilities), the impact of comorbidities, and emotional barriers (fear, shame, fatalism, avoidance, and low risk perception) inclusive of stigma. 36 - 39 To enable equitable participation, LCS programs need to address age, sex differences, current and past smoking status, socioeconomic status, and geographical factors. 38 …”
Section: Resultsmentioning
confidence: 99%
“…A PRISMA flow diagram of search results is presented in Figure 1 16 . Following screening, 32 articles were selected for inclusion; key characteristics are summarised in Table 2 6,17–47 . Study designs included RCTs ( n = 3), pre‐post studies ( n = 6), cross‐sectional studies ( n = 12), mixed‐methods studies ( n = 1), and qualitative studies ( n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…29 Regarding the LDCT scan experience, two studies reported that it was not an issue for most participants. 33,42 In one instance, compared with people most worried about the prospect of scanning or waiting for results, the few people who cited that they were most concerned about the actual LDCT experienced more discomfort during scanning. 42 The same study also found that those who reported dread or discomfort while waiting for their result had significantly worse anxiety and lung cancer-specific distress (but not health-related quality of life) overall than those who were not concerned about the result.…”
Section: Objective Service Delivery Componentsmentioning
confidence: 99%